Pengembangan Psikologi Positif dengan Metode PERMA pada Karyawan di Perumda Tirta Musi Palembang - Khaidir Riansyah; Sawi Sujarwo (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
This community service program aims to develop positive psychology among employees of Perumda Tirta Musi Palembang through the PERMA model approach. The method used in this community service program is descriptive quantitative to describe the positive psychology of employees based on the PERMA method among employees of Perumda Tirta Musi Palembang. The results of this community service show that all PERMA dimensions are in the good to high category. Employees are generally able to feel positive emotions, show high work engagement, establish harmonious interpersonal relationships, find meaning and purpose in their work, and achieve satisfying work accomplishments.